ENFORCEMENT OF REGIONAL REGULATIONS AS IMPLEMENTATION OF “SATPOL PP” DUTIES - Kusuma, Novian Eri (Universitas Airlangga, 2025)
In solving the problem of controlling street vendors, they require them to look at the problem from various aspects, and not only from one aspect. In this context, the Head of the Pamekasan Satpol PP which is an institution that carries out security and order in the community must continue to take corrective steps in all aspects of its activities, in order to improve the performance of its apparatus, considering that there will be more protests and complaints from both road users and residents. from the street vendors themselves who sell on the roadside. Based on the results of the research that the author did in the field, it turns out that the conditions for controlling street vendors are not firm, so it can be concluded that the ideal control of street vendors is difficult to realize, because in reality there are still Satpol PP officers in Pamekasan Regency who control street vendors with compassion and not have the heart to deal with traders whose stalls/businesses must be forcibly dismantled when there is a security and order raid.